Efectos del cromo hexavalente y un carbamato sobre dos especies de cladoceros (1999)
The effect of a carbamate and a heavy metal was evaluated on survival, sexual maturation and fertility of the acuatic cladocerans Daphnia magna and Daphnia obtusa. Alcute toxicity -LC50 and chronic toxicity-CV values were determined. For D. magna LC50 Cr+6 was 0.35 mg/l and CV 0.20 mg/l. For D. obtusa LC50 Cr+6 was 0.04 mg/l and VC 0.009 mg/l. For D. magna LC50 Methomyl was 0.10 mg/l and CV 2.2x10-3 mg/l. Exposure of D. obtusa to Methomyl yielded a LC50 of 0.005 mg/l, and response of animal at sublethal concentrations were irregular, therefore CV statistical confidence was poor and not show.